A novel method to interpret early phase trials shows how the narrowing of the coronary sinus concordantly improves symptoms, functional status and quality of life in refractory angina. Issue 1 (21st July 2020) - Jolicoeur, E Marc; Verheye, Stefan; Henry, Timothy D; Joseph, Lawrence; Doucet, Serge; White, Christopher J; Edelman, Elazer; Banai, Shmuel
Abstract : Background: Reduction of the coronary sinus was shown to improve angina in patients unsuitable for revascularisation. We assessed whether a percutaneous device that reduces the diameter of the coronary sinus improved outcomes across multiple endpoints in a phase II trial. Methods: We conducted a novel analysis performed as a post hoc efficacy analysis of the COSIRA (Co ronary Si nus R educer for Treatment of Refractory A ngina) trial, which enrolled patients with Canadian Cardiovascular Society (CCS) class 3–4 refractory angina. We used four domains: symptoms (CCS Angina Scale), functionality (total exercise duration), ischaemia (imaging) and health-related quality of life. For all domains, we specified a meaningful threshold for change. The primary endpoint was defined as a probability of ≥80% that the reducer exceeded the meaningful threshold on two or more domains (group-level analysis) or that the average efficacy score in the reducer group exceeded the sham control group by at least two points (patient-level analysis). Results: We randomised 104 participants to either a device that narrows to coronary sinus (n=52) or a sham implantation (n=52). The reducer group met the prespecified criteria for concordance at the group level and demonstrated improvement in symptoms (0.59 CCS grade, 95% credible interval (CrI)=0.22 to 0.95), total exercise duration (+27.9%, 95% CrI=2.8% to 59.8%) and quality of life (stability +11.2 points, 95% CrI=3.3 to 19.1; perception +11.0, 95% CrI=3.3 to 18.7). Conclusions: The reducer concordantly improved symptoms, functionality and quality of life compared with a sham intervention in patients with angina unsuitable for coronary revascularisation. Concordant analysis such as this one can help interpret early phase trials and guide the decision to pursue a clinical programme into a larger confirmatory trial. Trail registration number: ClinicalTrials.gov identifier: NCT01205893 .